The effects of the herbal medicine Daikenchuto (TJ-100) after esophageal cancer resection, open-label, randomized controlled trial - Nishino, Takeshi (Esophagus, 2017)
BACKGROUND: Daikenchuto (TJ-100), a traditional Japanese herbal medicine, is widely used in Japan. Its effects on gastrointestinal motility and microcirculation and its anti-inflammatory effect are known. The purpose of this prospective randomized controlled trial was to investigate the effect of TJ-100 after esophagectomy in esophageal cancer patients. METHODS: Forty patients for whom subtotal esophageal resection for esophageal cancer was planned at our institute from March 2011 to August 2013 were enrolled and divided into two groups at the point of determination of the operation schedule after informed consent was obtained: a TJ-100 (15 g/day)-treated group (n = 20) and a control group (n = 20). The primary efficacy end-points were maintenance of the nutrition condition and the recovery of gastrointestinal function. The secondary efficacy end-points were the serum C-reactive protein (CRP) level and adrenomedullin level during the postoperative course, the incidence of postoperative complications, and the length of hospital stay after surgery. RESULTS: We examined 39 patients because one patient in the TJ-100 group was judged as having unresectable cancer after surgery. The mean age of the TJ-100 group patients was significantly older than that of the control group patients.The rate of body weight decrease at postoperative day 21 was significantly suppressed in the TJ-100 group (3.6% vs. the control group: 7.0%, p = 0.014), but the serum albumin level was not significantly different between the groups. The recovery of gastrointestinal function regarding flatus, defecation, and oral intake showed no significant between-group differences, but postoperative bowel symptoms tended to be rare in the TJ-100 group. There was no significant between-group difference in the length of hospital stay after surgery. The serum CRP level at postoperative day 3 was 4.9 mg/dl in the TJ-100 group and 6.9 mg/dl in the control group, showing a tendency of a suppressed serum CRP level in the TJ-100 group (p = 0.126). The rate of increase in adrenomedullin tended to be high postoperatively, but there was no significant difference between the two groups. CONCLUSIONS: TJ-100 treatment after esophageal cancer resection has the effects of prompting the recovery of gastrointestinal motility and minimizing body weight loss, and it might suppress the excess inflammatory reaction related to surgery.